Role of biomarkers under endotelial and neuronal injury in ischemic stroke: a literature review (Research, Society and Development, 2023)
Stroke is an important cause of death and long-term disability. Ischemic stroke results from cerebral artery occlusion that decreases cerebral blood flow and causes rapid loss of brain function. Improvements in current treatments for cerebral ischemia are limited by many factors. A prothrombotic and embolic environment, exacerbated by inflammatory conditions, becomes a disposition for cerebrovascular blockage and ischemia. After this ischemic event, a cascade of secondary damage occurs resulting in the breakdown of the blood-brain barrier (BBB), which has been noted to be mediated by inflammation and oxidative stress, leading to an influx of immune cells destructive for proper neurological function. Therefore, the performance of biomarkers on endothelial injury in ischemic stroke was avaluated in the study. This is an integrative descriptive bibliographical review, in which electronic databases were used. The results found were several biomarkers that may be associated with vascular cerebral lesions and the risk of stroke, which would allow an early diagnosis, prognosis and risk stratification. However, it is important to emphasize that many of these biomarkers are still being studied and are not widely used in clinical practice, more research is needed to validate and deepen knowledge about these biomarkers and their application in the diagnosis and risk stratification of stroke.